La pedagogía socialista en la URSS : fundamentos para la configuración del individuo plenamente desarrollado. (2013)
This article presents the pedagogic models that took place in the URSS, with the ends of the socialist education. Although Marx and Engels had defined the polytechnic education as theoretical base, they didn’t have a pattern guide. The more debated categories were: the combination between the teaching and the work; the intervention grade for the development of a communist moral; and the establishment of the discipline like means or educational objective. It is appealed to three pedagogic proposals historically located: That formulated by Krupskaya, decanted in the complex method; the one enunciated by Makarenko starting from the coordination in two colonies for young; and the integrative perspective exposed by Suchodolski. Finally, the article shows a discussion about the existence of the school inside the socialism and the exercise of the socialist pedagogy in the capitalist society.